Proglacial river sediment fluxes in the southeastern Tibetan Plateau: Mingyong Glacier in the Upper Mekong River. Issue 11 (20th November 2022) - Lu, Xixi; Zhang, Ting; Hsia, Boey Lai; Li, Dongfeng; Fair, Heather; Niu, Hewen; Chua, Samuel D. X.; Li, Li; Li, Shaojuan
Abstract: Glacial and proglacial erosion are important sediment sources in river basins. The retreat of many glaciers on the Tibetan Plateau has important implications on the supply of fresh water and sediment dynamics for downstream river basins. Despite the importance of water and sediment dynamics at these catchments, existing quantification of suspended sediment fluxes from glacial catchments on the Tibetan Plateau is limited due to poor accessibility and challenging environments. This study presents the results of in‐situ investigations of water discharge and suspended sediment fluxes from the Mingyong Glacier catchment in Yunnan, Southwest China, between August 2013 and July 2017. The results show that the variation in water discharge and suspended sediment was highly seasonal. The variation of average suspended sediment concentration was large—69 ± 45; 119 ± 104; and 94 ± 97 mg/L in 2013, 2015, and 2016, respectively. We estimate that the sediment yield from the Mingyong catchment was highly variable ranging from 1104 t/km 2 /year in 2013 to 2281 t/km 2 /year in 2016, with 65%–78% of the total annual sediment load occurring during the summer (June to August). These annual variations in sediment yield can be attributed largely to precipitation patterns and extreme melting events. This study has provided a benchmark dataset that can be used for further works that investigate the impact of climate change on sediment dynamics in glacierized catchments in the Tibetan Plateau. Subsequently, the study helps us to better understand the increasing sediment supply to the Upper Mekong River from glacierized headwater catchments. Abstract : The water discharge and suspended sediment concentrations were measured over a three‐years period in the Mingyong Glacier catchment in Yunnan, Southwest China. The sediment yields from the Mingyong catchment were very high, ranging from 1, 104 t/km 2 /year in 2013 to 2, 281 t/ km 2 /year in 2016, with 65–78% of the total annual sediment load occurring during the summer (June to August).